2020
DOI: 10.1007/s41999-020-00421-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sleep quality, quantity and nutrition in oldest-old men The Helsinki Businessmen Study (HBS)

Abstract: Introduction Sleep quality and quantity often decline as people age, which may negatively impact health. We examined how nutrition is associated with self-reported sleep quality and quantity in oldest-old community-dwelling men. Methods In this cross-sectional analysis of the Helsinki Businessmen Study (HBS), a random sample of 130 surviving participants underwent a clinical examination in 2017–2018. Food and nutrient intakes were retrieved from 3-day food diaries in 126 men, and sleep quality and quantity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Several studies (not directly related to COVID-19) suggest that a plant-based diet rich in fruits and vegetables can lead to improved sleep quality [111,112]. The most recent example is the Helsinki Business study demonstrating an association between better sleep quality and vegetable consumption [113]. In contrast, a low-fiber and a high saturated fat intake were associated with lighter, less-restorative sleep [114].…”
Section: Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (not directly related to COVID-19) suggest that a plant-based diet rich in fruits and vegetables can lead to improved sleep quality [111,112]. The most recent example is the Helsinki Business study demonstrating an association between better sleep quality and vegetable consumption [113]. In contrast, a low-fiber and a high saturated fat intake were associated with lighter, less-restorative sleep [114].…”
Section: Sleep Qualitymentioning
confidence: 99%
“…Potential benefits with regard to long-COVID-related symptoms High in fiber [24][25][26] A low fiber intake was associated with lighter, less restorative sleep [113]; increasing fiber consumption may be beneficial with regard to long-COVID-related sleep disorders High in antioxidants and polyphenols (e.g., quercetin) [21,52,53] Naturally-occurring dietary polyphenols exhibit antidepressant activity [42] and may be beneficial with regard to long-COVID-related mental health problems Antioxidants neutralize free radicals and may help to tackle prolonged systemic inflammation often found in long-COVID [136] Polyphenols positively affect several cell types implicated in immune function [145] and exhibit direct antiviral properties [146,147] Favorable fatty acid profile [83] (high in polyunsaturated fatty acids [85], low in saturated fat, cholesterol and arachidonic acid [84])…”
Section: Features Of Plant-based Dietsmentioning
confidence: 99%
“…Higher vegetable intake was correlated with better sleep quality. In contrast, higher intake of sugars and saturated fatty acids showed a non-significant trend towards poorer sleep quality [ 47 ]. The above findings support the claim that a healthy diet can contribute to good sleep among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that these factors can be effective in improving sleep quality. Jyväkorpi et al Showed that eating vegetables helps to sleep better( 26 ). Hakkarainen et al Also showed that people with insomnia eat less vegetables( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Grandne et al, indicated that sugar consumption was directly related to poor sleep quality( 32 ). Jyväkorpi et al, Also showed that consumption of Sugars and Saturated Fats are associated to poor sleep quality( 26 ). Moreover, other animal and small human experimental studies have shown that high-saturated-fat diets may influence in circadian rhythms( 33 ).…”
Section: Discussionmentioning
confidence: 99%